Dinamika Kehidupan Sosial Masyarakat Transmigran Di Desa Gandasari, Tolangohula Tahun 1974-1998 - Mutia Sugara; Darwin Une (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to find out: first, how did the placement of transmigrants start in Gandasari village, Tolangohula in 1974. Second, how was the socio-economic development of the Javanese transmigrant community in Gandasari village in 1974-1998. The method used is historical research method. The research results are below Gandasari Village was a transmigration village in 1973-1975. Transmigration in this village occurred 3 times. The first group came from DKI Jakarta, the second came from Central Java, and the third came from West Java. Gandasari Village was not yet a village when the transmigration took place. Gandasari Village became a preparatory village in 1979 and became a definitive village in 1980. The transmigrant community received assistance from the government such as buildings, agricultural land, groceries and cash. This assistance is expected to ease the burden on transmigrants in new settlements. Keywords: Gandasari Village, Transmigration, Socio-Economy